2005
DOI: 10.1007/s10750-004-4426-x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny of oligochaetous Clitellata

Abstract: Clitellata, with more than one third of all annelid species described, is briefly introduced, and an overview of the hypotheses of phylogenetic relationships among the groups traditionally referred to as oligochaetes is given. The presentation is placed in a historical context and describes the trend to move from intuitive, narrative approaches to more formal analyses of character patterns. Monophyly of the earthworms (the megadriles, or Metagynophora sensu Jamieson), or at least a major part of them (Crassicl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 107 publications
(140 reference statements)
2
51
0
4
Order By: Relevance
“…The fauna of the subsidence ponds studied was composed of eleven benthic groups (Oligochaeta sensu oligochaetous clitellata (ERSÉUS, 2005), Gastropoda, Bivalvia, Hirudinea, Coleoptera, Heteroptera, Trichoptera, Ephemeroptera, Odonata, Diptera, Isopoda) among which oligochaetes predominated (more than 70% of the total benthic fauna). During the study 17 species representing the families Lumbriculidae (1 species), Enchytraeidae (1 species) and Naididae (15 species), in the new sense (ERSÉUS et al, 2008), were collected and identified.…”
Section: Resultsmentioning
confidence: 99%
“…The fauna of the subsidence ponds studied was composed of eleven benthic groups (Oligochaeta sensu oligochaetous clitellata (ERSÉUS, 2005), Gastropoda, Bivalvia, Hirudinea, Coleoptera, Heteroptera, Trichoptera, Ephemeroptera, Odonata, Diptera, Isopoda) among which oligochaetes predominated (more than 70% of the total benthic fauna). During the study 17 species representing the families Lumbriculidae (1 species), Enchytraeidae (1 species) and Naididae (15 species), in the new sense (ERSÉUS et al, 2008), were collected and identified.…”
Section: Resultsmentioning
confidence: 99%
“…Homology of the lecitotrophic early embryo would imply multiple loss and reversal in the lineages of Crassiclitellata and Hirudinea considering the current and generally accepted view of phylogeny within Clitellata (Erséus, 2005;Jamieson and Ferraguti, 2006;Sidall et al, 2006). For instance, all hirudineans including erpobdelliform leeches, which develop from oligolecithal eggs, form a derived group within the Hirudinea.…”
Section: Comparison Of Embryonic Muscle Patterns In Eisenia Andrei Ementioning
confidence: 99%
“…The phylogenetic relationships among Clitellata are still intensively discussed (Erséus, 2005;Jamieson and Ferraguti, 2006). A clitellum, comprising a single layer of cells, very likely represents the plesiomorphic state in Clitellata and is present in small aquatic oligochaetes often referred to as ''microdriles''.…”
Section: Introductionmentioning
confidence: 99%
“…Enchytraeidae is often regarded as a primarily terrestrial group, but it is probably the most ubiquitous of all clitellate families, with its more extreme habitats including glacial ice and deep-sea sediments (Erséus 2005). In the present study, the amphibious nature of many enchytraeid species is manifested, and the inclusion of the riparian zone does not only demonstrate that many enchytraeids prefer wet habitats, it also emphasizes the importance of the river banks in estimating the total species diversity of a river system.…”
Section: Discussionmentioning
confidence: 99%